Consistent survival benefit of enzalutamide plus androgen deprivation therapy in men with nonmetastatic castration-resistant prostate cancer: PROSPER subgroup analysis by age and region. (December 2021) - De Giorgi, Ugo; Hussain, Maha; Shore, Neal; Fizazi, Karim; Tombal, Bertrand; Penson, David; Saad, Fred; Efstathiou, Eleni; Madziarska, Katarzyna; Steinberg, Joyce; Sugg, Jennifer; Lin, Xun; et al.
Abstract: Background: Enzalutamide combined with androgen deprivation therapy (ADT) significantly prolonged metastasis-free survival and overall survival (OS) versus ADT alone in patients with non-metastatic castration-resistant prostate cancer (nmCRPC) with rapidly rising prostate-specific antigen (PSA). The objective of this post hoc analysis of the PROSPER trial is to evaluate OS benefit and safety of enzalutamide in patients across age and regional subgroups. Patients and methods: Eligible men with nmCRPC, PSA doubling time ≤10 months and PSA ≥2 ng/mL with continued ADT use were randomised 2:1 to enzalutamide 160 mg or placebo. OS and safety were examined by age (<70 vs ≥70 years) and region (North America, Europe, Asia or the rest of the world). The impact of prior and subsequent therapy was also examined. Results: In total, 1401 men were enrolled (median age, 74 years). Enzalutamide plus ADT reduced the risk of death, independent of age or region. Multivariate analyses identified Eastern Cooperative Oncology Group (ECOG) status (P < 0.0001), log (PSA; P = 0.0002) and subsequent therapy (P < 0.0001) as statistically significant factors impacting OS. Safety was consistent across age and regional subgroups. Any grade treatment-emergent adverse events were similar across age groups,  were more common in the placebo group and had regional variation. Conclusions: In men with nmCRPC and rapidly rising PSA, the benefit and safety of enzalutamide were consistent across age and regional subgroups. Variables impacting OS included ECOG status, log (PSA) and subsequent therapy. ClinicalTrials.gov identifier: NCT02003924 . Graphical abstract: Image 1 Highlights: Enzalutamide plus androgen deprivation therapy reduced the risk of death in non-metastatic castration-resistant prostate cancer. Overall survival with enzalutamide was similar across age and geographical regions. Three factors were identified that improved overall survival. The safety of enzalutamide was similar across age but varied with geography.